2007
DOI: 10.1002/pmic.200600900
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of dimorphic transition in the phytopathogenic fungus Ustilago maydis

Abstract: In the corn smut fungus Ustilago maydis, the dimorphic transition from budding to filamentous growth is intrinsically associated with the switch from a saprophytic to a pathogenic lifestyle. Both pathogenicity and filament formation are triggered by a heterodimeric homeodomain transcription factor encoded by the b mating type locus. Here, we present a reference map of the proteome of this dimorphic phytopathogenic fungus. Using 2-DE in combination with MALDI-TOF-MS and ESI-MS/MS, we were able to identify 250 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 46 publications
(65 reference statements)
1
48
0
3
Order By: Relevance
“…36 Previous studies with dimorphic fungi such as P. brasiliensis have demonstrated that these fungi require their morphological transitions for efficient adherence and invasion of the host to establish infection. 37 Morphological transitions in dimorphic fungi are highly complex events triggered by a wide range of environmental factors and consisting of a reversible change in the growth pattern, alternating between the unicellular yeast form and the filamentous form (hyphae and pseudohyphae). 38 Understanding the mechanisms that regulate these events is of extreme interest due to implications for pathogenesis and cell differentiation, as observed with the inhibition of the transition to the parasitic form by the female hormone estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…36 Previous studies with dimorphic fungi such as P. brasiliensis have demonstrated that these fungi require their morphological transitions for efficient adherence and invasion of the host to establish infection. 37 Morphological transitions in dimorphic fungi are highly complex events triggered by a wide range of environmental factors and consisting of a reversible change in the growth pattern, alternating between the unicellular yeast form and the filamentous form (hyphae and pseudohyphae). 38 Understanding the mechanisms that regulate these events is of extreme interest due to implications for pathogenesis and cell differentiation, as observed with the inhibition of the transition to the parasitic form by the female hormone estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Induction or suppression of the P crg1 promoter was carried out by growing cells in either YP (1% yeast extract and 2% peptone) or minimal medium (0.17% yeast nitrogen base [YNB] and 0.2% ammonium sulfate) supplemented with 2% arabinose or 2% dextrose, respectively (5). Similarly, induction or suppression of P nar1 promoter was achieved by growing cells in minimal media (0.17% yeast nitrogen base and 2% glucose) supplemented with 0.2% potassium nitrate (MMNO 3 medium) or 0.2% ammonium sulfate, respectively (4,5). Mating medium and solid medium were made with 1% activated charcoal and/or 2% agar (14).…”
Section: Methodsmentioning
confidence: 99%
“…In general, the transition between these alternate life forms means a complete turnover of cellular and proteomic components, which often involves cell cycle arrest and/or cytoskeletal rearrangement. Although the cellular proteomes associated with these two processes share many components, there are both temporal and spatial regulations that are manifested during the transitional phase (4).…”
mentioning
confidence: 99%
“…Previously, such approaches have been used to study phytopathogenic fungi through protein profiling (2,5,12,42,44) and to identify host- (45) and morphogenesis-responsive (25) proteins. Recent sequencing of the genomes of the phytopathogenic fungi Magnaporthe grisea, Ustilago maydis, Fusarium graminearum, and Stagonospora nodorum (7,9,19,24) provides an opportunity for more thorough mass spectrometry (MS)-based proteomic analyses (2,42).…”
mentioning
confidence: 99%